Effects of Brand Image, Product Quality, Price, and Customer Satisfaction on SIM Card User Loyalty Among University Students - Dilla Berliani; Novi Suri Hartati; Chindy Widya Ningsih (Jurnal Studi Multidisiplin Ilmu, 2024)
Purpose: The Indonesian telecommunications market is intensely competitive, and student consumers represent a strategically important segment for SIM card operators. This study investigates the effects of brand image, product quality, price, and customer satisfaction on Telkomsel SIM card user loyalty among undergraduate students of the Faculty of Economics and Business, Universitas Labuhanbatu.Methodology: A quantitative survey design was employed with a sample of 100 active Telkomsel SIM card users selected through convenience sampling. Primary data were collected using an online questionnaire with a five-point Likert scale. Classical assumption tests including normality, heteroscedasticity, and multicollinearity confirmed model eligibility.Results: The regression equation Y = 2.459 + 0.267X1 + 0.122X2 + 0.355X3 + 0.280X4 shows that brand image (t = 2.214, p = .029), price (t = 4.295, p = .000), and customer satisfaction (t = 4.063, p = .000) each exerted a positive and significant effect on loyalty. Product quality was directionally positive but did not reach significance (p = .057).Conclusions: Price and customer satisfaction are the dominant individual drivers of Telkomsel SIM card loyalty in the student segment. Brand image also contributes significantly, while product quality approaches but does not cross the significance threshold.Limitations: The convenience sample from a single university faculty, the cross-sectional design, and the absence of service quality as a predictor limit generalizability and model completeness.Contributions: This study provides empirical evidence of the relative importance of four loyalty determinants in the student telecommunications market in North Sumatra.